Brand society :How brands trasform management and lifestyle - Kornberger, Martin (Cambridge University Press, 2010)
"Think Coca-Cola. Think iPod. Think Nike. Think Google. Each of these names represents a successful product or service but, more importantly, they are all successful brands. Most attempts to explain the role of brands focus on brands either as management tools (managerial perspective) or as symptoms of consumerism (sociological perspective). In Brand Society, Martin Kornberger combines these perspectives to show how brands have the power to transform both the organizations that develop them and the lifestyles of the individuals who consume them. This holistic approach shows how brands function as a medium between producers and consumers in a way that is rapidly transforming our economy and society. Using an array of practical case studies from a diverse set of organizations, this book provides a fascinating account of the way in which brands influence the lives of individuals and the organizations they work in"--Provided by publisher.